Effects of natural extracts in cognitive function of healthy adults: a systematic review and network meta-analysis - Wang, Zhi-yuan; Deng, Ya-lu; Zhou, Ting-yuan; Liu, Yi; Cao, Yu (Frontiers in Pharmacology, 2025)
BackgroundFor years, diets and natural extracts have been explored for boosting cognition, but limited evidence challenges their recommendation for widespread use.ObjectiveOur study aimed to perform a network meta-analysis to evaluate effects of natural extracts on cognitive function in healthy adults. Methods: Researchers reviewed randomized controlled trials from Embase, PubMed, Cochrane Library, and Web of Science (up to 7 September 2024). Study quality was assessed with the Cochrane Risk of Bias Tool, and node-splitting analysis ensured consistency (p > 0.05). SUCRA values were calculated using parametric bootstrapping with 10,000 resamples. Primary outcomes included global cognition, attention, memory, executive function, and cognitive flexibility, with efficacy ranked by SUCRA probabilities.ResultsFrom 27 studies with 2,334 samples and 19 natural extract treatments, RPTW showed the greatest improvement in overall cognition (SUCRA: 95.9%). No extracts significantly outperformed placebo for attention. CG (Cistanche + Ginkgo biloba) was most effective for memory (SUCRA: 89.3%), executive function (SUCRA: 96.9%), and cognitive flexibility (SUCRA: 98.0%).ConclusionRPTW extracts improve overall cognition in healthy adults, while CG enhances memory, executive function, and cognitive flexibility.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-11-0007/, identifier INPLASY (INPLASY2024110007).